2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

Nanostructured tin oxide: synthesis and gas-sensing properties - Niranjan, R. S.; Hwang, Young Kyu; Kim, D. K.; Jhung, S. H.; Chang, J. S.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2005)
Pure and Ru-doped nanostructured SnO2 sensing materials were synthesized using a modified Pechini route. Incorporation of Ru in SnO2 results in the reduction of particle size (8.3 nm) compared with that of the pure SnO2 (28.2 nm). Moreover, the sensor exhibited a reasonably good sensitivity towards both H-2 and liquified petroleum gas (LPG). The effect of Ru incorporation, operating temperature, and gas concentration on the structure, morphology, and sensitivity is discussed using the results of X-ray diffraction (XRD), and scanning electron microscopy (SEM) along with sensing performance. © 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen and hydrocarbon sensor; Nanostructure; ruthenium; tin oxide

New synthetic approach to a [1.1.6] metapara cyclophane derivative via Suzuki-Miyaura cross-coupling and ring-closing metathesis - Kotha, S; Mandal, K; Arora, KK; Pedireddi, R (Advanced Synthesis & Catalysis, 2005)
The synthesis of a [1.1.6] metapara cyclophane derivative, 1,5(1,4),3(1,3)-tribenzenacycloun-decaphan-8-ene-6,11-dione, has been achieved via the Suzuki-Miyaura cross-coupling of alpha,alpha'-dibromo-m-xylene with an arylboronic acid derivative followed by an allylation and ring-closing metathesis reaction sequence.
Keywords: Cyclophanes; olefin metathesis; Palladium; ruthenium; Suzuki-Miyaura cross-coupling

Valence-state analysis through spectroelectrochemistry in a series of quinonoid-bridged diruthenium complexes [(acac)(2)Ru(mu-L)Ru(acac)(2)](n) (n =+2,+1, 0,-1,-2) - Ghumaan, Sandeep; Sarkar, Biprajit; Maji, Somnath; Puranik, Vedavati G.; Fiedler, Jan; Urbanos, Francisco A.; Jimenez-Aparicio, Reyes; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry-A European Journal, 2008)
The quinonoid ligand-bridged diruthenium compounds [(acac)(2)Ru(mu-L2-)Ru(acac)(2)] (acac(-) = acetylacetonato = 2,4-pentanedionato; L2- = 2,5-dioxido-1,4-benzoquinone, 1; 3,6-dichloro-2,5-dioxido-1,4-benzoquinone, 2; 5,8-dioxido-1,4-naphthoquinone, 3; 2-3-dichloro-5,8-dioxido-1,4-naphthoquinone, 4; 1,5-dioxido-9,10-anthraquinone, 5; and 1,5-diimido-9,10-anthraquinone, 6) were prepared and characterized analytically. The crystal structure analysis of 5 in the rac configuration reveals two tris(2,4-pentanedionato)ruthenium moieties with an extended anthracenedione-derived bis(ketoenolatee) pi-conjugated bridging ligand. The weakly antiferro-magnetically coupled {Ru-III(mu-L2-)Ru–(III)} configuration in 1-6 exhibits complicated overall magnetic and EPR responses,. ne simultaneous presence of highly redox-active quinonoid-bridging ligands and of two ruthenium centers capable of adopting the oxidation states +2, +3, and +4 creates a large variety of possible oxidation state combinations. Accordingly. the complexes 1-6 exhibit two reversible one-electron oxidation steps and at least two reversible reduction processes. Shifts to positive potentials were observed on introduction of Cl substituents (1 -> 2, 3 -> 4) or through replacement of NH by O (6 -> 5). The ligand-to-metal charge transfer (LMCT) absorptions in the visible region of the neutral molecules become more intense and shifted to lower energies on stepwise reduction with two electrons. On oxidation, the para-substituted systems 1-4 exhibit monocation intermediates with intervalence charge transfer (IVCT) transitions of (RuRuIV)-Ru-III mixed-valent species. In contrast, the differently substituted systems 5 and 6 show no such near infrared (NIR) absorption. While the first reduction steps are thus assigned to largely ligand-centered processes, the oxidation appears to involve metal-ligand delocalized molecular orbitals with variable degrees of mixing.
Keywords: magnetic properties; quinones; ruthenium; spectroelectrochemistry; structure elucidation; valence-state distributions

Investigations on Ru doped ZnO: strain calculations and gas sensing study - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
Pure and ruthenium (Ru) doped nano-crystalline zinc oxide (ZnO) powders were synthesized by using well-known citrate gel route. Citric acid acts as a chelating agent and thus helps in the formation of nanoparticles. The detailed X-ray diffraction (XRD) studies using Hall equation reveal that in the nanoscale dimensions, incorporation of Ru modulates the lattice strain. It is interesting to note that on Ru doping, the compressive strain present in the undoped ZnO changes into tensile strain. We have tested the response of these specimens individually for reducing gases like H(2), LPG (liquefied petroleum gas), C(2)H(5)OH (ethanol), CO, acetone and oxidizing gases like NO, and Cl(2). Undoped ZnO responses perceptibly to LPG while Ru doped sample highly senses ethanol vapors. This might be due to either change in composition on Ru doping or/and difference between basicity of LPG and C(2)H(5)OH vapors. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Ethanol sensor; LPG sensor; Nanomaterials; ruthenium

Efficient heterogeneous catalytic system for chemoselective hydrogenation of unsaturated ketones in aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Polyhedron, 2010)
A highly chemoselective and green heterogeneous catalytic system of immobilized Ru(II)-phenanthroline complexes on amino functionalised MCM-41 material for the chemoselective hydrogenation of unsaturated ketones to unsaturated alcohols is demonstrated using water as a solvent The XRD and FTIR spectra show the highly ordered hexagonal nature of the MCM-41 even after encapsulation of the ruthenium complex The complex retains its configuration after anchoring as was confirmed by FTIR and UV-Vis analysis The detailed reaction parametric effect was studied for the hydrogenation of 3 methylpent-3-en-2-one to achieve complete conversion up to >99% chemoselectivity of 3-methylpent-3-en-2 ol The anchored heterogeneous catalysts were recycled effectively and reused five times with marginal changes in activity and selectivity The use of water as a solvent not only afforded high activity for the hydroge nation reaction compared to organic solvents but also afforded a green process Crown Copyright (C) 2010 Published by Elsevier Ltd All rights reserved
Keywords: 1 10 Phenanthroline; alpha beta Unsaturated ketone; Chemoselective hydrogenation; mesoporous materials; ruthenium

Heterogenized Ru(II) phenanthroline complex for chemoselective hydrogenation of diketones under biphasic aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Journal of Molecular Catalysis A-Chemical, 2010)
The chemoselective hydrogenation of acetylacetone to 4-hydroxypentan-2-one over immobilized ruthenium phenanthroline metal complexes in amino functionalized MCM-41 in biphasic aqueous reaction medium was investigated. The catalyst was characterized by XRD, TEM, surface analysis, FT-IR and UV-vis to understand the morphology, complex geometry, and XPS such that the oxidation state of the metal complex inside the MCM-41 framework could be understood. The use of water as a solvent, not only gives high activity and selectivity for hydrogenation of acetylacetone, but also gives a path for an environmentally safer process. The optimizations of ligand, metal to ligand ratio, the choice of solvent and other reaction parameters were studied in detail. The heterogeneous catalytic system gave a higher degree of chemoselectivity (99%) towards 4-hydroxypentan-2-one as compared to homogeneous catalyst when hydrogenation was carried out using water as a solvent. The immobilized ruthenium-phenanthroline complex was easily separated and reused. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 4-Hydroxypentan-2-one; acetylacetone; Chemoselective; Diketone; Hydrogenation; Phenanthroline; ruthenium; Water

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Ruthenium-catalyzed C6-propenylation reactions of substituted pyridine derivatives: directed and direct C-H activation - Goriya, Yogesh; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
Keywords: alkenylation; C?H activation; nitrogen heterocycles; pyridine derivatives; ruthenium

Hydrogenation of polar bonds catalysed by ruthenium-pincer complexes - Balaraman, Ekambaram; Milstein, David (Ruthenium in Catalysis, 2014)
Catalytic hydrogenation of polar bonds using molecular hydrogen is an important, atom-economical synthetic reaction. Classical reduction methods of polar bond often require reactive metal-hydride reagents in stoichiometric amount and produce copious waste. Hydrogenation of carbonyl compounds in particular provides `green' approaches to synthetically important building blocks, such as alcohols and amines. We have designed and synthesized several ruthenium-based pincer catalysts for unprecedented hydrogenation reactions including: (1) amides to alcohols and amines, (2) biomass-derived di-esters to 1,2-diols and (3) CO2 and CO derivatives to methanol. These atom-economical reactions operate under neutral, homogeneous conditions, at mild temperatures, mild hydrogen pressures, and can operate in absence of solvent with no generation of waste. The postulated mechanisms involve metal-ligand cooperation (MLC) by aromatization-dearomatization of the heteroaromatic pincer core.
Keywords: Amides; Carbon dioxide; Esters; Hydrogen; Hydrogenation; Metal-ligand cooperation; Pincer complexes; ruthenium

Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium

Ruthenium-catalyzed deconstruction of polyolefins: a strategy to up-cycle waste polyethylene to value-added alkene - Padhi, Ganeshdev; Khopade, Kishor V.; Moyilla, Nageswararao; Rangappa, Raghavendrakumar; Chikkali, Samir H.; Barsu, Nagaraju (Angewandte Chemie-International Edition, 2025)
Synthesis of value-added products from post-consumer waste polyolefins is fascinating as well as challenging. Here we report ruthenium-catalyzed up-cycling of the polyethylene to long-chain alkene derivatives. The developed methodology mainly involves two steps i.e., dehydrogenation of polyethylene through hydrogen atom transfer and its metathesis using the HG-II catalyst. The dehydrogenation of polyethylene using ruthenium catalysis derived up to 3.38 %, of double bonds; with 90 % of the recovered polyolefin material. The obtained unsaturated polyethylene was subjected to cross-metathesis with ethylene using HG-II catalytic system. This resulted in the synthesis of predominantly dodecene (C12) derivatives, with 58 % selectivity, along with other derivatives of varying chain lengths. The overall reaction produced terminal and internal olefins in the ratio 1:0.8 respectively. The dehydrogenation of polyethylene and its deconstruction was confirmed by NMR spectroscopy, Gel Permeation Chromatography (GPC) and Differential Scanning Calorimetry (DSC). The origin of C12 selectivity has been demonstrated by control experiments. The scope of the methodology was extended to post-consumer waste polyethylene which gave high conversion to value-added dodecene derivatives as a major product.
Keywords: Deconstruction; Homogeneous catalysis; ruthenium; Upcycling; Waste plastic